2017
DOI: 10.1245/s10434-016-5742-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Chemical Pyloroplasty Necessary for Minimally Invasive Esophagectomy?

Abstract: In a well-matched cohort study with a historical control group, use of botulinum toxin for chemical pyloroplasty in minimally invasive esophagectomies was not associated with improved outcomes related to the pylorus versus no pyloric intervention. Although preliminary, these data suggest that chemical pyloroplasty is not necessary in minimally invasive esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, Eldaif et al [39] reported that although the use of IPBT significantly decreased the operative time compared to pyloromyotomy and pyloroplasty, the patients who received IPBT suffered from more reflux symptoms, had more frequent use of promotility drugs, needed more frequent endoscopic pyloric interventions, and had no benefits compared to those who underwent pyloromyotomy and pyloroplasty in terms of reducing dumping symptoms. In a well-matched cohort study, Stewart et al [40] demonstrated a similar incidence of DGE between patients who received no pyloric intervention and those who received IPBT in the setting of minimally invasive esophagectomy.…”
Section: Managementmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Eldaif et al [39] reported that although the use of IPBT significantly decreased the operative time compared to pyloromyotomy and pyloroplasty, the patients who received IPBT suffered from more reflux symptoms, had more frequent use of promotility drugs, needed more frequent endoscopic pyloric interventions, and had no benefits compared to those who underwent pyloromyotomy and pyloroplasty in terms of reducing dumping symptoms. In a well-matched cohort study, Stewart et al [40] demonstrated a similar incidence of DGE between patients who received no pyloric intervention and those who received IPBT in the setting of minimally invasive esophagectomy.…”
Section: Managementmentioning
confidence: 92%
“…Each method has its advantages and disadvantages, so we cannot say with certainty which one is the best. However, advocates for the no-intervention strategy have been gradually reporting convincing results [40,55,56].…”
Section: Pyloric Drainage Proceduresmentioning
confidence: 99%
“…Botulinum injection is associated with higher rates of reflux symptoms (35). When compared directly to patients with no intraoperative pyloric intervention, rates of delayed gastric emptying were equivalent in both groups and there was no significant difference in need for additional pyloric procedure (36).…”
Section: Pylorusmentioning
confidence: 98%
“…Furthermore, a study doubted the necessity of IBTJ in minimally invasive esophagectomy patients as both IBTJ and no-intervention controlled group had low incidence of DGE (IBTJ: 8.6%, 3/35 vs. Controlled: 5.6%, 2/36) (19). Fortunately, a phase II RCT (NCT02965976) is recruiting patients to answer this unsolved problem and hopefully we will know whether we should perform IBTJ in esophagectomy patients before long.…”
Section: Ibtjmentioning
confidence: 99%